An interview with Sir John Parker, Chairman, National Grid - Kakabadse, Andrew P. (Emerald Group Publishing Limited, 2007)
This article aims to capture latest thinking from an internationally renowned practitioner on the themes of Chairmanship, purpose of the board and governance.
Keywords: Boards of Directors; Chairmen; Governance; Leadership; Risk management